Penyuluhan Pada Ibu Hamil Sebagai Upaya Meningkatkan Pengetahuan tentang Prenatal Yoga di PMB Permata Banyuasin - Wahyu Ernawati; Intan Sari; Ratna Dewi; Bina Aquari; Ahmad Arif (JURNAL PENGABDIAN KADER BANGSA, 2025)
Pregnancy is a reproductive process that requires special attention so that it runs smoothly because it involves the lives of the mother and fetus (Elisabeth, 2020). Prenatal yoga is one way to prepare mothers physically and psychologically, including reducing anxiety before giving birth. Prenatal Yoga helps expectant mothers prepare themselves to face childbirth with confidence, happiness, comfort, without fear, as well as strengthening and forming body posture. The aim of this service is to increase the knowledge and participation of pregnant women in carrying out prenatal yoga exercises to improve health and reduce discomfort during pregnancy. The steps for this activity consist of establishing relationships, submitting proposals and setting schedules, as well as involving an evaluation process with a question and answer session. This counseling includes lecture methods, discussions, practices, and audio-visual media during prenatal yoga. The result of this community service activity is that 60% of pregnant women had poor knowledge about prenatal yoga before receiving counseling. After being provided with information about prenatal yoga, the knowledge of pregnant women increased by about 90%. The recommendation from the community service group to pregnant women is to improve their health by practicing prenatal yoga, including body movements and breathing techniques that can provide a relaxing effect, help reduce physical stress, and facilitate the delivery process.